Nasal and Sinus Disorders in Patients with Primary Acquired Nasolacrimal Duct Obstruction (PANDO) - Mohammad Sharifi (Patient Safety and Quality Improvement Journal)
Introduction:To investigate the frequency of nasal and sinus problems in patients with acquired nasolacrimal duct obstruction.Materials and Methods: The prospective case-control study was performed on 44 patients with primary acquired nasolacrimal duct obstruction, who were referred to oculoplastic clinics for surgery, and 50 healthy controls. All patients were evaluated with nasal endoscopy by an otolaryngologist. All endoscopic data were reported, including secretion from the middle meatus, nasal deviation, presence of a mass or polyp, turbinate hypertrophy, and concha bollosa.Results: The mean age of the patients was 42.02±12.04 years. The majority of participants were female (70.45%). 72.7% (32/44) of the PANDO group had varying sinus and nasal disorders. Septal deviation was the most common accompanying disorder, and it was found to be in 61.4 % (27/44) of the PANDO group compared to 36% (18/50; P=0.03) of the controls. 77.77% (28/36) of patients with unilateral nasolacrimal duct obstruction had been associated with sinus and nasal disorders.Conclusion:Due to the high frequency of nasal and sinus disorders in patients with acquired nasolacrimal duct obstruction, otolaryngology consultation before surgery is recommended.